Recent regional warming across the Siberian lowlands: a comparison between permafrost and non-permafrost areas - Ping Wang; Qiwei Huang; Shiqi Liu; Hongyan Cai; Jingjie Yu; Tianye Wang; Xiaolong Chen; Sergey P Pozdniakov (Environmental Research Letters, 2022)
The northern mid-high latitudes experience climate warming much faster than the global average. However, the difference in the temperature change rates between permafrost and non-permafrost zones remains unclear. In this study, we investigated the temporal changes in temperature means and extremes across the Siberian lowlands (<500 m) over the past six decades (1960–2019) using in situ observations and reanalysis data. The results show that permafrost zones (0.39 °C/decade) have warmed faster than non-permafrost zones (0.31 °C/decade). The minimum values of the daily maximum ( TXn ) and minimum ( TNn ) temperatures changed faster than their maximum values ( TXx, TNx ), suggesting that low minimum temperatures increase faster, as evidenced by the considerably higher warming rate in the cool season (October–April, 0.43 ± 0.10 °C/decade, n = 126) than that in the warm season (May–September, 0.25 ± 0.08 °C/decade, n = 119). The change rates of TXx and TNx in permafrost areas were 2–3 times greater than those in non-permafrost areas; however, over the last ten years, TXx and TNx in non-permafrost areas showed decreasing trends. Moreover, faster-warming permafrost regions do not exhibit a faster increase in surface net solar radiation than slower-warming non-permafrost regions. While our findings suggest that carbon emissions from thawing soils are likely a potential driver of rapid warming in permafrost-dominated regions, the potential feedback between ground thawing and climate warming in permafrost regions remains uncertain.